Cytokine Levels in Late Pregnancy: Are Female Infants Better Protected Against Inflammation? - Burns, Christine; Hall, Sharron Therese; Smith, Roger; Blackwell, Caroline (Frontiers in Immunology, 2015)
Inflammatory responses have been implicated in several forms of infant deaths (sudden expected deaths and stillbirths) and the initiation of pre-term births. In this study, we examined matched samples of term maternal blood, cord blood, and amniotic fluid obtained from 24 elective cesarean deliveries for both pro- and anti-inflammatory cytokines thought to be important in maintaining a balanced response leading to successful pregnancy outcome. These included interleukin (IL)-1β, IL-6, IL-8, tumor necrosis factor-α (TNF-α), interferon-γ (IFN-γ), IL-10, and IL-1 receptor antagonist (IL-1ra). Amniotic fluid levels for each of the cytokines examined were significantly higher than those for cord blood or maternal plasma. While pro-inflammatory cytokines were higher in amniotic fluid associated with male fetuses compared with females, the major significant difference was higher levels of IL-1ra in amniotic fluid associated with female fetuses. Our study supports similar findings for cytokines during mid-trimester, which noted that amniotic fluid levels were higher than those in maternal blood. Our study suggests that maternal decidua secretes additional IL-ra in the presence of a female conceptus which improves the likelihood of a good outcome compared to pregnancies with male fetuses.